Phase-I and randomized phase-II trial of panobinostat in combination with ICE (ifosfamide, carboplatin, etoposide) in relapsed or refractory classical Hodgkin lymphoma. Issue 4 (3rd April 2018) - Hu, Bei; Younes, Anas; Westin, Jason R.; Turturro, Francesco; Claret, Linda; Feng, Lei; Fowler, Nathan; Neelapu, Sattva; Romaguera, Jorge; Hagemeister, Fredrick B.; Rodriguez, Maria Alma; Samaniego, Felipe; et al.
Abstract: This phase-I/phase-II study evaluated panobinostat in combination with ifosfamide, carboplatin, etoposide (P-ICE) in relapsed/refractory classical Hodgkin lymphoma. During phase I, panobinostat was given daily on Monday/Wednesday/Friday starting one week prior to Cycle 1 (C1) of ICE and during two weeks of C1-2 of ICE (Schedule A). No DLT was observed at 30 mg. However, frequent (84%) grade-4 thrombocytopenia during second week prompted us to omit the second week of panobinostat 30 mg (Schedule B) for phase II, where this regimen was compared to ICE. In the randomized phase-II study, CR was seen in 9/11 (82%) and 8/12 (67%) for P-ICE and ICE, respectively ( p = .64). Grade-4 neutropenia (55% vs. 8%) and thrombocytopenia (100% vs. 33%) were more common in P-ICE. In summary, combination therapy using panobinostat produced high CR rate at the cost of greater bone marrow toxicity. Investigation of panobinostat with less myelosuppressive agents is of interest.